Fasciíte necrotizante limitada a região pré-peritoneal - Coelho,Júlio Cezar Uili (1998)
Our objective is to report a case of a patient with necrosis limited to the pre-peritoneal fascia and fat tissue of the abdomen and pelvis. A 34-year-old female presented with fever, chills, nausea, diarrhea and abdominal pain. She denies history of trauma, diabetes mellitus, use of immunosuppressive drugs, smoking, and drug dependence. Laboratory tests revealed hematocrit of 28.7%, white blood count of 12.200/mm3 with 49% of bands, platelets of 317.000/mm3, and sedimentation rate of 65 mm/hr. She was subjected to an abdominal ultrasonography and computed tomography that showed hepatosplenomegaly and muscular thickening on the left flank. Surgical debridment was performed. There was necrosis limited to the pre-peritoneal fascia and fat tissue extending from the pelvis to the left flank. The fascia of the superficial muscles and the subcutaneous fat were normal. The pathologic examination showed suppuration and necrosis of the tissues. Antibiotics were administered and ten debridments were performed. The patient was discharged 30 days after the admission.